The Relationship Between Teachers’ Demographic Profiles And Teachers’ Perception Towards The Internal Quality Assurance Assessment At Program Level In Two Secondary High Schools In Laiza And Mai Ja Yang Townships, Kachin State, Myanmar. - Tun, Aung Ya; Ye, Yan (Scholar: Human Sciences, 2019)
The purpose of this study was to determine the teachers’ perception towards Internal Quality Assurance (IQA) Assessment at program level and relationship with the teachers’ demographic factors: age, educational qualification, years of service in school, and academic rank in two Secondary High Schools in Laiza and Mai Ja Yang Townships, Kachin State, Myanmar, and to compare teachers’ perception towards internal quality assurance system according to teachers’ gender. Two set of questionnaires were used to conduct this study: Questionnaires for teachers’ demographic profile and Questionnaires for Internal Quality Assurance (IQA) Assessment at Program Level. 95% of the questionnaires were returned valid and data were analyzed by frequency, percentage, mean, standard deviation, and Pearson’s Product Moment Correlation Coefficient (r). The findings of objectives were that the teachers’ perception towards total internal quality assurance system based on fifteen components was at low level. Therefore, there was no significant difference between male teachers and female teachers’ perception towards internal quality assurance system according to teachers’ gender. There was no significant relationship between internal quality assurance system at program level and other teachers’ demographic factors. Since all the significant values were bigger than .05 at the significant level. The study recommended that school’s principals and board committee members should pay more attention to focus on IQA strategic planning and implementation process in order for promoting schools’ quality.